IMPLEMENTASI KEBIJAKAN STANDAR KESELAMATAN PELAYARAN DI KABUPATEN BANGGAI LAUT - Sono, Aldi; Djaelangkara, Rizali; Tawil, Yulizar Pramudika (JPS: Journal of Publicness Studies, 2025)
This research aims to find out the title of the Implementation of Shipping Safety Standards Policy in Banggai Laut Regency. The theory used is Charles O. Jones. This type of research is descriptive research and the basis of the research used is qualitative. Informants were determined using purposive sampling with as many informants as possible 8 People. The data collection techniques used are observation, in-depth informal interviews and documentation to collect the required data in the form of primary and secondary data. Data analysis is carried out by reducing data, data modeling (data display), drawing/verifying conclusions. Data Validity Check Using Source Triangulation. The results of this research can be concluded that the implementation of the Shipping Safety Standards Policy in Banggai Laut Regency is hampered by a lack of human resources and inadequate safety equipment, even though there is a clear organizational structure. Effective policy implementation is highly dependent on the availability and quality of resources, requiring increased outreach and training to ensure that both personnel and the public have adequate safety information and equipment.